An investigation on the dissimilar friction stir welding of T-joints between AA5754 aluminum alloy and poly(methyl methacrylate). (February 2019) - Derazkola, Hamed Aghajani; Simchi, Abdolreza
Abstract: Process optimization to prepare T-joints of poly methyl methacrylate (PMMA) and AA5754 alloy by friction stir welding (FSW) was performed. Effects of processing parameters including tool rotational velocity, traverse speed, tilt angle and plunge depth (TP) were studied. The material flow and formation of interaction layer upon FSW were evaluated and the tensile strength and hardness of the joints were examined. It is shown that by controlling the heat input into stir zone through increasing the rotational velocity or decreasing travelling speed, less defects are formed while the thickness of the interaction layer increases. The optimum condition is attained at 1600 rpm/30 mm min −1 with a tool tilt angle of 2° and plunge depth of 0.2 mm. Under this condition, the joint strength would reach ~71% (50 MPa) of the base polymer. It has been found that the thickness of the interaction layer and formation of internal voids have a remarkable influence on the strength and hardness of the T-joints. The presented results could be useful for development of dissimilar FSW of metal/polymer joints. Highlights: The new T-connection between the AA5754 aluminum alloy and PMMA was performed by friction stir welding (FSW) method. Mechanical and metallurgical properties of joint investigated and discussed about relation between FSW parameters with T- joint properties. The optimum FSW process parameters introduced to achieve highest mechanical properties of joint.